Fecal microbiome composition and lactic acid bacteria in Senduro goats revealed by 16S rRNA gene sequencing - GUNTUR TRIMULYONO; SALAMUN SALAMUN; FATIMAH FATIMAH; ALMANDO GERALDI (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Trimulyono G, Salamun, Fatimah, Geraldi A. 2026. Fecal microbiome composition and lactic acid bacteria in Senduro goats revealed by 16S rRNA gene sequencing. Biodiversitas 27 (5): d270522. https://doi.org/10.13057/biodiv/d270522. Senduro goat (Capra hircus) is an important breed widely cultivated in Senduro District, Lumajang Regency, East Java, Indonesia. This study aimed to describe the fecal microbiome composition and lactic acid bacteria (LAB) detected in Senduro goats from two age groups (1-2 months and 4-5 years) using 16S rRNA gene sequencing. The 16S rRNA gene amplicons from goat fecal samples were sequenced using next-generation sequencing (NGS), targeting the V3-V4 region. Based on descriptive analysis of two composite samples, variation in microbial diversity indices and taxonomic composition was observed between the two samples. Firmicutes and Bacteroidota were the dominant phyla in both samples, while several other taxa varied between the two samples. In the fecal samples of kid goats, the dominant phyla included Firmicutes, Bacteroidota, Actinobacteriota, Proteobacteria, Campylobacterota, and Fusobacteriota. In the fecal samples of adult goats (FKD), the dominant phyla were Firmicutes, Bacteroidota, Spirochaetota, Verrucomicrobiota, Fibrobacterota, and Desulfobacterota. LAB belonging to the genera Streptococcus, Lactobacillus, Ligilactobacillus, Limosilactobacillus, and HT002 were detected only in the kid goat sample (FKA), indicating variation in gut microbial composition between the two samples and providing preliminary insight into potential microbial candidates associated with early gut colonization in Senduro goats. Because each group was represented by a single composite sample, these findings should be interpreted as preliminary descriptive observations rather than evidence of age-related differences. This study provides baseline information on the fecal microbiome composition of Senduro goats and highlights the need for future studies with adequate biological replication and integrated functional analyses.